Experience as the focus of development: A proposal for the training of social pedagogues. - Blanco García, Nieves; Sierra Nieto, Jose Eduardo (Education Policy Analysis Archives, 2013)
The meaning of initial training is to help the students to develop their own ways of thinking, acting, explaining and reflecting on the principles that guide their actions. We therefore believe that our role as teachers is to encourage the students to develop their own ways of thinking and acting based on their own "lived´s experiences". From these assumptions, we've develop a training proposal that builds on the experience: that of students: ours as teachers and that of professional educators. In the pages that follow, we discuss the concepts that guide ours principles and methodological options, and some reflections on the challenges and possibilities that open.